Perbanyakan dan Aplikasi PGPR (Plant Growth Promoting Rhizobactheria) di Laboratorium Pengamatan Hama dan Penyakit Banyumas - Nada Kholifah; Ardiana Kartika B; Teguh Pribadi (UM Purwokerto Press, 2021)
PGPR (Plant Growth Promoting Rhizobacteria) is a substance that helps plant growth with the help of rhizosphere microorganisms. PGPR propagation can be done with liquid media. This PGPR propagation needs to be done because this substance has many benefits for agricultural cultivation. The application of PGPR to the test plant, namely the pakcoy plant, proved that there was an effect of giving PGPR to the plant. Observations on the test plants were carried out by observing several observation variables such as plant height, root length, number of leaves, wet weight and dry weight. The results of these observations showed that the effect on the test plants was seen in the variables of root length, wet weight, and dry weight. Meanwhile, the variable plant height and number of leaves did not show a visible difference.